The effect of digital infrastructure on export technological complexity in manufacturing: Empirical evidence from China 2011-2023 - Dandan, Xu; Asmat, Ismail Nor (Journal of Asian Scientific Research, 2025)
Existing research has mainly focused on export volume or performance, with relatively limited discussion of the impact of technological complexity on manufacturing products. This study utilizes panel data from 30 provincial regions in China from 2011 to 2023 and systematically assesses the impact of digital infrastructure on the technological complexity of manufacturing exports using a fixed-effects panel model and mediation analysis. It further conducts a comprehensive investigation from the perspectives of transmission mechanisms and regional heterogeneity. Empirical results show that digital infrastructure significantly enhances the technological sophistication of manufacturing exports, with a 1% increase in digital infrastructure associated with an average 0.394% rise in export sophistication. The results are statistically significant and robust across various specifications. Besides, heterogeneity analysis highlights that the beneficial influence is particularly evident in both eastern and western regions, accompanied by greater marginal effects in areas characterized by limited digital infrastructure development. Furthermore, the mediation analysis demonstrates that digital infrastructure indirectly enhances export technological complexity by promoting technological progress and human capital accumulation. This study offers empirical evidence for understanding the evolution of manufacturing export competitiveness under the digital economy and provides policy implications for optimizing regional digital infrastructure allocation and promoting high-quality export development.